Cheese consumption and risk of cardiovascular disease: a meta-analysis of prospective studies - Chen, Guo-Chong; Wang, Yan; Tong, Xing; Szeto, Ignatius M. Y.; Smit, Gerrit; Li, Zeng-Ning; Qin, Li-Qiang (European journal of nutrition, 2017)
Purpose Cheese contains a high content of saturated fatty acids but also lists of potentially beneficial nutrients. How long-term cheese consumption affects the development of cardiovascular disease (CVD) is unclear. A meta-analysis of prospective observational studies was conducted to evaluate the risks of total CVD, coronary heart disease (CHD), and stroke associated with cheese consumption. Methods Potentially eligible studies were identified by searching PubMed and EMBASE databases and by carefully reviewing the bibliographies of retrieved publications and related reviews. The summary relative risks (RRs) with 95 % confidence intervals (CIs) were calculated using the random-effects model. Results The final analyses included 15 prospective studies. Most of the studies excluded prevalent CVD at baseline (14/15) and had a duration >10 years (13/15). The summary RR for high vs. low cheese consumption was 0.90 (95 % CI 0.82–0.99) for total CVD (7 studies, 8076 events), 0.86 (95 % CI 0.77–0.96) for CHD (8 studies, 7631 events), and 0.90 (95 % CI 0.84–0.97) for stroke (7 studies, 10,449 events), respectively. The restricted cubic model indicated evidence of nonlinear relationships between cheese consumption and risks of total CVD ( P nonlinearity < 0.001) and stroke ( P nonlinearity = 0.015), with the largest risk reductions observed at the consumption of approximately 40 g/d. Conclusions This meta-analysis of prospective studies suggests a nonlinear inverse association between cheese consumption and risk of CVD.